(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this research, the structural and electrical properties of the ZNS membrane were studied at a pure 5nm (100,200,300) range prepared by a thermochemical spray method at room temperature on hot glass (450°C) and at a spray rate (2.5 mL/min), and the effect of the fish and metallicity at 500°C) on these properties for one hour. X-ray diffraction results have shown that all prepared diaphragms have a multiple crystallization (quadripartite) and predominant orientation (002, 211, 200, 101, 110) structure for all models before and after metamorphism, and that metamorphism increased the grain size As for electrical properties, the study included the calculation of electrical conducation as a function of temperature within the range ( ºc 25-150 ). The results showed two wake-up energies ( EA1,EA2 ), which indicate two delivery mechanisms. One is in low (25–85°C) and the other in temperature It is also known that the number of people who have been in the United States has increased from the number of people who have been in the United States since the end of the year to the end of the year is higher than the number of people who have been in the United States.